Three-dimensional structure of the yeast ribosome. - Verschoor, A (1998)
The 80S ribosome from Saccharomyces cerevisiae has been reconstructed from cryo electron micrographs to a resolution of 35 A. It is strikingly similar to the 70S ribosome from Escherichia coli, while displaying the characteristic eukaryotic features familiar from reconstructions of ribosomes from higher eukaryotes. Aside from the elaboration of a number of peripherally located features on the two subunits and greater overall size, the largest difference between the yeast and E.coli ribosomes is in a mass increase on one side of the large (60S) subunit. It thus appears more elliptical than the characteristically globular 50S subunit from E.coli. The interior of the 60S subunit reveals a variable diameter tunnel spanning the subunit between the interface canyon and a site on the lower back of the subunit, presumably the exit site through which the nascent polypeptide chain emerges from the ribosome.